Fica Fícus na cidade de Belo Horizonte (2013-2016): informação, ação e possibilidades para construção de uma coleção digital - Jose Nunes do Nascimento (2016)
In this work we approach the history of Belo Horizonte, built upon processes of redefinitions of the public spaces. The constructions and destructions of the citys built environments are lost in time, without records that include the actors participating in these dynamics. In the multiplicity of perspectives, we looked at the city under the environmental perspective and realized that the logic of the administration considers the citys trees as obstacles to progress. Thus, we propose to create a digital collection for the environmental movement Fica Fícus, intending to reconstruct a dimension that makes possible to experience the city through the establishment of green spaces. Therefore, with a digital collection based on database, we try to experience the city through the environmental perspective of the trees, removing from anonymity actors and events, to work against forgetting the past, bringing up elements for building a more accurate story.